Using mathematical research methods for analyzing environmental and economic prospects of the Russian arctic oil and gas producing shelf projects - O. V. Kudryavtseva; E. V. Serebrennikov (Russian Journal of Economics and Law)
Objective: to study the ecological and economic prospects of Russian Arctic oil and gas offshore projects by the method of functional analysis.Methods: mathematical modeling, comparative analysis, empirical analysis.Results: a method is proposed for assessing the financial provision of measures to eliminate the alleged environmental damage caused by hydrocarbon spills in Arctic offshore oil and gas production projects; models of oil spills in the “Prirazlomnoye” and “Pobeda” Arctic offshore fields are considered; the cost of measures to eliminate these incidents is estimated.Scientific novelty: for the first time, the paper investigates the function of financial provision for measures to eliminate the alleged environmental damage due to hydrocarbons spills at the “Prirazlomnoye” and “Pobeda” Arctic offshore oil and gas fields with the mathematical method of functional analysis, calculation of the maximum costs, as well as the time from the start of the spill, which accounts for these functional values. The assumption of the mathematical model is the hypothesis of the constancy of the well flow rate (the top estimate is the characteristic flow rate of the per second production of the entire field), as well as the neglect of changes in the physical properties of liquid hydrocarbons (viscosity, density) due to the characteristic annual temperature dynamics of the Arctic regions and consideration of the dynamics of the oil spill spread on the sea surface in the inert phase without taking into account the gravitationally viscous and surface modes.Practical significance: the mathematical modeling data on spills can be used by insurance companies in the calculation of insurance premiums, by Rosprirodnadzor Agency in the calculation of fines, and by other supervisory agencies in the underwriting of oil and gas Arctic projects.